Diversification along a benthic to pelagic gradient contributes to fish diversity in the world's largest lake (Lake Baikal, Russia). Issue 1 (17th October 2021) - St. John, Carl A.; Buser, Thaddaeus J.; Kee, Victoria E.; Kirilchik, Sergei; Bogdanov, Bakhtiar; Neely, David; Sandel, Michael; Aguilar, Andres
Abstract: Insights into the generation of diversity in both plants and animals have relied heavily on studying speciation in adaptive radiations. Russia's Lake Baikal has facilitated a putative adaptive radiation of cottid fishes (sculpins), some of which are highly specialized to inhabit novel niches created by the lake's unique geology and ecology. Here, we test evolutionary relationships and novel morphological adaptation in a piece of this radiation: the Baikal cottid genus, Cottocomephorus, a morphologically derived benthopelagic genus of three described species. We used a combination of mitochondrial DNA and restriction site associated DNA sequencing from all Cottocomephorus species. Analysis of mitochondrial cytochrome b haplotypes was only able to two resolve two lineages: C . grewingkii and C . comephoroides / inermis . Phylogenetic inference, principal component analysis, and faststructure of genome‐wide SNPs uncovered three lineages within Cottocomephorus : C . comephoroides, C . inermis and C . grewingkii . We found recent divergence and admixture between C . comephoroides and C . inermis and deep divergence between these two species and C . grewingkii . Contrasting other fish radiations, we found no evidence of ancient hybridization among Cottocomephorus species. Digital morphology revealed highly derived pelagic phenotypes that reflect divergence by specialization to the benthopelagic niche in Cottocomephorus . Among Cottocomephorus species, we found evidence of ongoing adaptation to the pelagic zone. This pattern highlights the importance of speciation along a benthic‐pelagic gradient seen in Cottocomephorus and across other adaptive fish radiations.